1983
DOI: 10.1007/bf00598906
|View full text |Cite
|
Sign up to set email alerts
|

Cholescintigraphy with99mTc-diethyl-IDA for the detection of rejection of auxiliary liver transplants in pigs

Abstract: In 15 pigs an auxiliary liver was transplanted and cholescintigraphy with 99mTc-diethyl-IDA was performed to study the function of the livers separately. Serial scintigraphy of the recipient and donor liver was performed on days 3, 8 and 18 after transplantation and time-activity curves over 1 h after injection of the radio-tracer were generated for each liver. From these data the time at which the maximal activity was present in the liver (Tmax) and the time at which during the excretion phase half of this ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Results of cholescintigraphy with iminodiacetic acid (IDA) analogues in liver transplants have been compared with liver biopsies in animals (Cuervas-Mons et al 1987;deJonge et al 1983). DeJonge et al (1983) showed that technetium-99m diisopropyMDA (DISIDA) excretion was delayed in all pigs with signs of rejection and normal in those with normal biopsies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of cholescintigraphy with iminodiacetic acid (IDA) analogues in liver transplants have been compared with liver biopsies in animals (Cuervas-Mons et al 1987;deJonge et al 1983). DeJonge et al (1983) showed that technetium-99m diisopropyMDA (DISIDA) excretion was delayed in all pigs with signs of rejection and normal in those with normal biopsies.…”
Section: Introductionmentioning
confidence: 99%
“…DeJonge et al (1983) showed that technetium-99m diisopropyMDA (DISIDA) excretion was delayed in all pigs with signs of rejection and normal in those with normal biopsies.…”
Section: Introductionmentioning
confidence: 99%